MicroRNA-218 promotes cisplatin resistance in oral cancer via the PPP2R5A/Wnt signaling pathway - Zhuang, Zehang (Oncol Rep, 2017)
Accumulating data suggest that microRNAs (miRNAs) play a pivotal role in the regulation of tumor cell sensitivity to chemotherapeutic agents. Although the roles of a few miRNAs have been identified in cisplatin resistance, little is known in regards to the concerted contribution of miRNA-mediated biological networks. In the present study, we demonstrated that microRNA-218 (miR-218) was significantly upregulated in cisplatin-resistant oral cancer cells. The results of cell viability and apoptosis assay showed that ectopic expression of miR-218 induced cell survival and resistance to cisplatin, whereas suppression of miR-218 caused apoptosis and enhanced sensitivity to cisplatin. Moreover, we identified PPP2R5A as a new direct target of miR-218 by using the dual luciferase reporter assay. Overexpression of miR-218 led to inhibition of PPP2R5A expression, whereas knockdown of miR-218 increased PPP2R5A levels. Introduction of PPP2R5A abrogated miR-218-mediated cell survival and drug resistance. Furthermore, suppression of miR-218 or PPP2R5A significantly promoted or reduced cisplatin-induced apoptosis, respectively. Finally, PPP2R5A overexpression or β-catenin knockdown inhibited miR-218-mediated Wnt activation and partially restored cell sensitivity. Our data revealed a molecular link between miR-218 and PPP2R5A/Wnt signaling and implicates miR-218 as a potential target for oral cancer therapy.